Stigma, Habitus, and Higher Education: Delegitimizing University Pathways in a Coastal Community of Indonesia - Syahputra, M. Adrian; Saragi, Muhammad Putra Dinata (TEMALI : Jurnal Pembangunan Sosial, 2026)
This study analyzes how stigma toward higher education is produced and sustained in the coastal community of Perupuk Village, Batu Bara Regency, North Sumatra. The article argues that low participation in higher education is not determined solely by economic constraints and access, but by social processes that delegitimize higher education as a life choice perceived as impractical and uncertain. Using a qualitative approach, the study draws on field observations and interviews with fifteen informants consisting of working youth and parents. The findings show that the community recognizes higher education as symbolically valuable—as a marker of intelligence and social status—yet weakens it in practice through family- and community-level risk calculations. Community members perceive higher education as costly, long-term, and lacking guarantees of employment, especially when contrasted with coastal work that provides immediate income and visibly contributes to household livelihoods.Stigma emerges through everyday social interactions, including evaluative community language, the circulation of narratives about unemployed university graduates, early-work culture, and family norms, which collectively frame work as the safest, most realistic, and most meaningful life orientation. Drawing on the social stigma theory of Crocker, Major, and Steele, the article demonstrates that stigma operates as a collective symbolic mechanism that lowers the legitimacy of the identity of prospective students/students. Bourdieu’s concept of habitus helps explain why this delegitimation appears natural and stable: dispositions toward early work, shaped by coastal lived experience, reproduce preferences for short-term returns and suppress long-term educational investment. Practically, efforts to increase higher education participation in coastal areas require interventions that go beyond financial assistance to include cultural-symbolic strategies that restore the legitimacy of higher education as a viable life pathway.